Critical transport and critical scattering in ﬂuids - Folk, R. (Condensed Matter Physics, 2000)
We consider the critical properties of ﬂuids induced by the critical ﬂuctuations in the order parameter. The theory describes the crossover from the analytic background behaviour to the universal asymptotic behaviour of several dynamic quantities.